Experimental and numerical studies of the processes of spraying coal-water slurries with pneumatic nozzle - Gvozdyakov D. V. Dmitry Vasilievich; Zenkov A. V. Andrey Viktorovich; Kondakov A. A. Aleksandr Aleksandrovich; Maltsev L. I. Leonid Ivanovich; Podzharov Yu. S. Yury Sergeevich (2024, 2024)
Title screen